Integration of geochemical and geophysical approaches for the assessment of seawater intrusion on groundwater for agricultural purposes / Mohamad Faizal Tajul Baharuddin - Tajul Baharuddin, Mohamad Faizal (2015)
Groundwater contamination is a serious issue because it depletes fresh groundwater resources. Groundwater resources in coastal areas are susceptible to seawater intrusion given its close proximity to sea. Seawater intrusion can induce salinity, which affects groundwater resources and agriculture activities along coastal areas. This situation becomes more severe in island coastal areas as the primary water resources are mainly from freshwater lenses. This study aims to assess the impact of seawater intrusion into groundwater aquifer and agriculture activities in island coastal areas. Groundwater salinity in a Malaysian island coastal area was assessed by using a geo-electrical-and-geochemical integrated technique in combination with surface and subsurface hydrogeology study. The effect of groundwater salinity on the agricultural cultivations, especially of oil palm plants, has not been examined previously. The integrated technique was applied to the coastal area of Carey Island in Selangor, Malaysia, which is the biggest island in Malaysia whose inhabitants cultivate oil palm plants as a major income source. A large part of the island (the west and south areas) is near the Straits of Malacca and is thus exposed to seawater intrusion, which can deteriorate the quality of the fresh groundwater aquifer. A subsurface hydrogeology study revealed that the aquifer system in Carey Island consists of semi-confined and unconfined aquifer systems. The unconfined aquifer (sandy material) was located at the edge of Carey Island (near the sea). The amount of total dissolved solids (TDS) in groundwater of unconfined aquifer in the east was twice that in groundwater in the west. Groundwater chemistry, conductivity, and time lapse electrical resistivity tomography measurements showed that groundwater in this area was affected by seawater. The integrated technique established the relationship between subsurface resistivity and geochemistry and generated an empirical equation. Three groundwater salinity degree were identified, namely, fresh (휌푒>10.0 .m), brackish (3.0 .m<휌푒<10.0 .m), and saline (휌푒<3.0 .m). The freshwater lens thicknesses in the mid-east and mid-west areas, which were located alongside one another laterally in 3-D resistivity slice images, varied. Freshwater in the mid-west area was 30m deep except in the mangrove reserve area, whereas freshwater in the mid-east was only 10 m deep. The 3-D conductivity slice images also revealed a difference in groundwater salinity levels between the mid-east and mid-west areas. The obtained conductivity values of 31 m (mid-west) and 14 m (mid-east) were unsuitable for oil palm plantation. Groundwater in the study area may no longer be suitable for oil palm plantation in the 21st century based on predictions regarding local sea-level increase and the Ghyben-Herzberg assumption. The groundwater salinity variation between the east and west is attributed to contrasts in surface elevation, land cover and drainage distribution system. These contrasts contributed to the difference in seawater intrusion effect on each area. The integration technique successfully classified oil palm suitability by using TDS values as follows: TDS < 5,300mg/L is suitable; 5,300 mg/L < TDS < 12,000mg/L is moderately suitable; and TDS > 12,000mg/L is unsuitable. The integration technique successfully determined the impact of seawater intrusion into groundwater aquifer and oil palm cultivation affected by groundwater salinity. This technique can also be used to determine the effect of groundwater salinity on other socioeconomic activities in coastal areas.